Prevention of White Spot Lesions Induced by Fixed Orthodontic Therapy: A Literature Review - Francesco Saverio Ludovichetti; Edoardo Stellini; Andrea Zuccon; Patrizia Lucchi; Niccolò Dessupoiu; Sergio Mazzoleni; Roberta Gaia Parcianello (Dentistry Journal)
Objectives: This study aims to review the scientific literature on the prevention of white spot lesions (WSLs) associated with fixed orthodontic treatment. WSLs result from enamel demineralization and pose aesthetic and functional challenges. The study evaluates the effectiveness of various preventive interventions to reduce the risk of WSLs during orthodontic care. Methods: A comprehensive literature search was conducted using MeSH terms such as “white spot”, “fixed orthodontic treatment”, “CPP-ACP”, “topical fluoride”, and “demineralized lesion”, combined with the Boolean operator ‘AND’. Databases searched included PubMed, EMBASE, Scopus, and OpenGrey, focusing on studies published between January 2014 and September 2024. The inclusion criteria required studies to evaluate interventions aimed at reducing WSL risk in patients undergoing fixed orthodontic treatment. A total of 41 articles were screened, with 17 selected based on relevance and methodological rigor. Results: The review identified several effective strategies for preventing WSLs. Topical fluoride applications, particularly high-concentration varnishes, significantly reduced WSL prevalence, with some studies favoring fluoride varnish over other interventions. CPP-ACP and CPP-ACPF formulations demonstrated potential for remineralizing demineralized enamel, especially when combined with fluoride toothpaste. High-fluoride toothpaste and acidulated phosphate fluoride mouthwash were effective in reducing lesion incidence, emphasizing the importance of patient compliance in daily oral hygiene routines. Professional interventions, such as fluoride varnish applications, showed enhanced outcomes when re-applied periodically. Conclusions: Preventing WSLs during orthodontic treatment is crucial for ensuring the aesthetic and functional success of therapy. Strategies combining fluoride-based interventions with casein phosphopeptide formulations offer significant benefits. However, patient education and adherence to recommended oral hygiene practices remain critical. Further research is needed to compare the long-term effectiveness of these interventions and to explore new technologies for WSL prevention.